2017
DOI: 10.14295/transportes.v25i4.1055
|View full text |Cite
|
Sign up to set email alerts
|

Estudo do comportamento do revestimento de pavimento utilizando mistura asfáltica morna com adição de borracha moída de pneu na SPA-248/055

Abstract: Este artigo apresenta um estudo realizado com mistura asfáltica morna utilizando ligante aditivado com agente surfactante e borracha moída de pneus. Foram feitos ensaios para verificar o comportamento mecânico de mistura de concreto asfáltico com asfalto-borracha morno e foi comparado com uma mistura de referência, de concreto asfáltico com asfalto-borracha usinado a quente. A primeira apresentou resultado satisfatório, dentro dos limites de norma. Adicionalmente, realizou-se a análise das emissões de poluente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…The ITS of the mixture with 14% oil to the asphalt binder experienced a 57% decrease of ITS compared to an asphalt mixture with neat binder. Merighi and Suzuki (2017) also observed that a WMA presented ITS lower than the reference hot asphalt mixture. According to these authors, the reductions in ITS are associated with an increase in the volume of voids in the WMA.…”
Section: Indirect Tensile Strength (Its)mentioning
confidence: 74%
“…The ITS of the mixture with 14% oil to the asphalt binder experienced a 57% decrease of ITS compared to an asphalt mixture with neat binder. Merighi and Suzuki (2017) also observed that a WMA presented ITS lower than the reference hot asphalt mixture. According to these authors, the reductions in ITS are associated with an increase in the volume of voids in the WMA.…”
Section: Indirect Tensile Strength (Its)mentioning
confidence: 74%
“…In these tanks, the main emissions are total organic carbons (TOCs), volatile organic compounds (VOCs), and polycyclic aromatic hydrocarbons (PAHs) (BERNUCCI et al, 2008;RUBIO et al, 2013;ZANETTI et al, 2016;MERIGHI and SUZUKI, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Existem diferentes tipos de aditivos para as misturas mornas no mercado, variando de produtos quıḿicos e orgânicos, asfalto espuma a ceras orgânicas (MERIGHI, 2017). No entanto, segundo Stimilli (2017) cada tipo de aditivo, empregado na fabricação das misturas WMA, atua com base em mecanismos particulares que fornecem benefıćios e desvantagens especı́ icas.…”
Section: Introductionunclassified